Improved Fire Disaster Mitigation Efforts through Nursing Disaster Education among a Boarding School Students and Teachers at Surakarta City - Zam, Bagus Muhammad Iqbal Al Zam; Harnanto, Addi Mardi; Widodo, Widodo; Sunarto, Sunarto; Sumardino, Sumardino (Basic and Applied Nursing Research Journal, 2022)
Disaster events are also very risky to occur in the school area. The most common danger in school is fire. School disaster management includes the familiar procedural cycle found in planning and implementation of physical risk mitigation, safe facility maintenance, standard operating procedures, and disaster response training. This study aims to analyze the effect of nursing disaster education on increasing fire disaster mitigation efforts among students and teachers of a boarding school in Surakarta City. The research employed one group pretest posttest design. Sampling technique in this study was purposive sampling with the application of inclusion and exclusion criteria. The number of research samples was obtained by 64 respondents. The instruments in this study were questionnaires to find out the level of knowledge and attitudes of the level of fire disaster mitigation efforts. The hypothesis test used was the Paired T-test on the knowledge sub variable and Wilcoxon on the attitude sub variable. The study found both knowledge and attitude towards fire catastrophe mitigation improved between the pretest and posttest. The improvement in knowledge was 3.9 points, whereas the improvement in attitude was 4. The Sig result was 0.00 based on the t-test analysis of the knowledge sub variable. Furthermore, the Sig result was 0.00 based on the Wilcoxon analysis of attitude sub variable.It can be concluded that Nursing Disaster Education has an effect in improving fire disaster mitigation efforts in students and teachers in high schools.